Key performance indicators : developing, implementing, and using winning KPIs - Parmenter, David (Wiley, 2015)
"Streamline KPIs to craft a simpler, more effective system of performance measurementKey Performance Indicators provides an in-depth look at how KPIs can be most effectively used to assess and drive organizational performance. Now in its third edition, this bestselling guide provides a model for simplifying KPIs and avoiding the pitfalls ready to trap the unprepared organization. New information includes guidance toward defining critical success factors, project leader essentials, new tools including worksheets and questionnaires, and real-world case studies that illustrate the practical application of the strategies presented. The book includes a variety of templates, checklists, and performance measures to help streamline processes, and is fully supported by the author's website to provide even more in-depth information. Key Performance Indicators are a set of measures that focus on the factors most critical to an organization's success. Most companies have too many, rendering the strategy ineffective due to overwhelming complexity. Key Performance Indicators guides readers toward simplification, paring down to the most fundamental issues to better define and measure progress toward goals. Readers will learn to: separate out performance measures between those that can be tied to a team and result in a follow-up phone call (performance measures) and those that are a summation of a number of teams working together (result indicators) look for and eradicate those measures that have a damaging unintended consequence, a major darkside Sell a KPI project to the Board, the CEO, and the senior management team using best practice leading change techniques Develop and use KPIs effectively with a simple five stage model Ascertain essential performance measures, and develop a reporting strategy Learn the things that a KPI project leader needs to know A KPI project is a chance at a legacy - the project leader, facilitator, or coordinator savvy enough to craft a winning strategy can affect the organization for years to come. KPI projects entail some risk, but this book works to minimize that risk by arming stakeholders with the tools and information they need up front. Key Performance Indicators helps leaders shape a performance measurement initiative that works"--